Designing a Model for Enhancing Organizational Efficiency with an Emphasis on the Role of Social Network Marketing at Pegah Company - Ansari, Amirhossein; Ansari, Azarnoush; Abzari, Mehdi; Dasineh, Mehdi; Rostamijaz, Hamid (Business, Marketing, and Finance Open, 2025)
The aim of this study is to design a model for enhancing organizational efficiency with an emphasis on the role of social network marketing at Pegah Company. A qualitative research method was employed to examine the hypotheses and address the research questions. To gather information on the theoretical foundations and literature, as well as to extract variables affecting organizational efficiency, extensive library research was conducted. This included reviewing Persian and English books, peer-reviewed articles, Internet sources, and related studies in the field. Additionally, semi-structured interviews were conducted to identify relevant variables. The study population comprised experts in the dairy industry and digital marketing specialists. Purposive sampling was used, and the sample size was determined by the theoretical saturation of the research questions; in this study, the final sample consisted of 15 participants. Thematic analysis (TA) was utilized to evaluate the hypotheses and answer the research questions. TA is a method for analyzing qualitative data that focuses on identifying patterns of meaning within a dataset. This process involves recognizing recurring themes within the qualitative data. By synthesizing the extracted variables through a comprehensive literature review and interviews with experts, and by organizing and categorizing these variables using thematic analysis, a model was developed indicating that two primary factors influence organizational efficiency. These two main factors are: (a) Social Network Marketing and (b) the Efficiency of Social Network Marketing. The Social Network Marketing factor comprises several sub-variables, including the efficiency and effectiveness of the social network, the company’s capability and credibility, the utilization of appropriate information within the network, the trust of network members in the network’s security, the participation of network members in information sharing, the use of suitable network content, and the financial support for marketing activities in social networks. Similarly, the Efficiency of Social Network Marketing factor consists of multiple sub-variables, including the company’s adaptability to the market environment, its social network marketing strategy, its approach to utilizing digital platforms, the perception of customer needs, the perceived quality of products, management performance, and the perceived quality of services.